Ask Question
30 March, 08:52

Solve: - 6 (-2) : 4 (-3)

0
Answers (1)
  1. 30 March, 10:21
    0
    -9

    Step-by-step explanation:

    Simplify the following:

    -6 * (-2) / 4 (-3)

    -6 * (-2) / 4 (-3) = (-6 (-2) (-3)) / 4:

    (-6 (-2) (-3)) / 4

    The gcd of - 2 and 4 is 2, so (-6 (-2) (-3)) / 4 = (-6 (2 (-1)) (-3)) / (2*2) = 2/2 * (-6 (-1) (-3)) / 2 = (-6 (-1) (-3)) / 2:

    (-6-1 (-3)) / 2

    (-6) / 2 = (2 (-3)) / 2 = - 3:

    --3 (-3)

    -3 (-1) = 3:

    3 (-3)

    3 (-3) = - 9:

    Answer: - 9
Know the Answer?